Measuring and improving corporate governance in China using clsa standard. - Choy, Hui Shan. (2008)
With the rising number of corporate scandals in the world today, the notion of good corporate governance is of greater importance more than ever. In the midst of several standards of corporate governance available, we seek to explore the differences between two existing corporate governance standards, and the reasons behind China's low corporate governance score thereby expanding into ways to rectify China's current situation. This study compares two models of corporate governance standards namely, from Standard & Poor's (S&P) and Credit Lyonnaise Securities Association (CLSA). We will also analyze China's failure under the CLSA standard. Finally, the paper will discuss prospective areas for studies in future.